The Effect of Mobile Emission on Ambient Air Quality in Perlis - Siti Hawa Abu Bakar (School of Environmental Engineering, University Malaysia Perlis, 2016)
To evaluate the pattern of motor vehicles statistics in Perlis. To evaluate the emission loading from mobile sources in Perlis. To evaluate the emission of carbon dioxide (CO2) from mobile sources in Perlis.